2021
DOI: 10.1038/s41419-021-04193-7
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circ_0043280 inhibits cervical cancer tumor growth and metastasis via miR-203a-3p/PAQR3 axis

Abstract: Circular RNAs (circRNAs) are known to act as key regulators in a variety of malignancies. However, the role of circRNAs in cervical cancer (CCa) remains largely unknown. Herein, we demonstrated that a circRNA derived from the TADA2A gene (hsa_circ_0043280) was significantly downregulated in CCa and that this reduction in expression was correlated with a poor prognosis. Furthermore, our results demonstrated that hsa_circ_0043280 functions as a tumor suppressor to inhibit tumor growth and metastasis in CCa. Mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…Circ_0003204 overexpression resulted in CC cell growth and invasion promotion [ 35 ]. Differently, circSmarca5 and circ_0043280 served as cancer inhibitors for CC development [ 36 , 37 ]. In this study, we detected the significant upregulation of circ_0008460 in CC.…”
Section: Discussionmentioning
confidence: 99%
“…Circ_0003204 overexpression resulted in CC cell growth and invasion promotion [ 35 ]. Differently, circSmarca5 and circ_0043280 served as cancer inhibitors for CC development [ 36 , 37 ]. In this study, we detected the significant upregulation of circ_0008460 in CC.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has identified circVPRBP (hsa_circ_0065898) as a 367-base circRNA down-regulated in CCa [27], as sanger sequence showed the back splicing site of the circVPRBP (Fig. 1A).…”
Section: Circvprbp Expression Is Downregulated During Cca Ln Metastasismentioning
confidence: 96%
“…qRT-PCR, RT-PCR, gel electrophoresis, IHC, western blotting, and HE staining, were performed as described previously [5,27,42]. The primary antibodies used in this study are given in Supplementary Table S4.…”
Section: Qrt-pcr Rt-pcr Gel Electrophoresis Immunohistochemistry (Ihc...mentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs are rich in miRNAs binding sites and competitively repress transcriptional regulation of miRNAs, a new class of highly expressed and stable ceRNAs ( Shi et al, 2013 ). The cyclic RNA hsa_circ_0043280 can reduce PAQR3 levels by competitively absorbing miR-203a-3p and blocking miR-203a-3p, and can function as a tumor suppressor to inhibit tumor growth and metastasis in cervical cancer ( Zhang et al, 2021b ). Hsa_circ_0006349 promotes MKP1 expression through uptake of miR-98, which enhances proliferation and glycolysis of non-small-cell lung cancer (NSCLC) cells and promotes malignant progression of tumors ( Qin et al, 2021 ).…”
Section: Biological Functions Of Circular Rnasmentioning
confidence: 99%